Deciphering the Dynamics: A Self-Report Correlational Investigation into Workplace Stress, Procrastination, and Job Satisfaction amongst Employees at Academic Institution - Wei, Li-Wei (Journal of China-ASEAN Studies, 2024)
The study leverages a robust empirical framework, analyzing data from a meticulously curated cohort of 217 Chinese nationality teachers employed at a private university specializing in science and technology. The research sample, characterized by a balanced gender distribution and diverse educational attainment, provides a comprehensive foundation for examining the multifaceted impacts of stress on occupational outcomes. Employing validated instruments such as the Job Stress Scale, Procrastination at Work Scale (PAWS), and the Overall Job Satisfaction measure, this study elucidates the nuanced gender-specific and educational level-based patterns in stress, procrastination, and job satisfaction. The findings reveal significant gender disparities, with males reporting lower job stress but higher procrastination and lower job satisfaction compared to their female counterparts, who exhibit elevated stress yet maintain higher job satisfaction and lower procrastination. Furthermore, the study delineates the correlation between educational attainment and the observed variables, highlighting that higher educational levels correlate with increased job stress but improved procrastination management and sustained high job satisfaction. Through rigorous statistical analyses, including Pearson correlation and regression models, the research substantiates the inverse relationship between workplace stress and both procrastination behavior and job satisfaction, reinforcing the imperative for tailored organizational interventions. This investigation not only contributes to the existing body of knowledge but also underscores the critical need for gender-sensitive and educational level-specific strategies to mitigate workplace stress and enhance job satisfaction, thereby fostering a healthier and more productive academic workforce.